Behavior and impact of polyamide nylon to the indoor air quality during SLS powder handling process - Muhamad Damanhuri, Amir Abdullah; Hariri, Azian; Nordin, Normayati (Penerbit UTHM, 2020)
The increasing trend associated with Additive Manufacturing (AM) on the application of polyamide-nylon in selective laser sintering (SLS) prototype printing is due to economic and environmental factors. However, number of conducted researches regarding the hazard of exposure to human from powder handling during 3D printing process is very limited especially in the usage of polyamide nylon powder. The emitted particles from the SLS powder handling process were found as a cause to respiratory and cardiovascular disruptions including asthma and lung cancer to the operators. Given AM technology is one of the key focus areas under the National Policy on Industry 4.0, this study aims to support the 4th strategy of Occupational Safety and Health Master Plan 2016-2020 in protecting workers rights to a safe, healthy and conducive working environment. Usually, SLS requires operators to mix virgin and recycle powder or known as refresh rate to feed into SLS chamber. The usage of several type of polyamide nylon which is virgin, recycle and mix powder (refresh rate) appear to be a potential source of dust concentration. This research undergoes characterization to investigates the behaviour of polyamide nylon powder (PA12) in terms of morphology and particle size distribution of polyamide nylon. ..